2021
DOI: 10.5826/dpc.1103a57
|View full text |Cite
|
Sign up to set email alerts
|

FotoFinder Dermoscopy Analysis and Histopathological Correlation in Primary Localized Cutaneous Amyloidosis

Abstract: Background: Primary localized cutaneous amyloidosis (PLCA) causes extracellular proteinaceous deposits in skin. It is clinically divided into macular amyloidosis, lichen amyloidosis and nodular amyloidosis. Atypical presentations of PLCA make the diagnosis challenging, requiring biopsy to confirm amyloid deposition in the upper papillary dermis. Objectives: This study used FotoFinder dermoscopy to characterize lichen and macular amyloidosis and correlated the dermoscopic features with histopathological fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…To analyze the dermoscopic findings in different variants of PCA, we performed a comprehensive search of three medical databases (PubMed, Web of Science, and Scopus) using the search terms ‘dermoscopy’ or ‘dermatoscopy’ combined with ‘primary cutaneous amyloidosis’ or ‘macular amyloidosis’ or ‘lichen amyloidosis’ or ‘nodular amyloidosis’ or ‘biphasic amyloidosis’ or ‘amyloidosis cutis dyschromica’. In total, twelve articles, including three original studies and nine case reports, were identified [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The dermoscopic characteristics of PCA are summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To analyze the dermoscopic findings in different variants of PCA, we performed a comprehensive search of three medical databases (PubMed, Web of Science, and Scopus) using the search terms ‘dermoscopy’ or ‘dermatoscopy’ combined with ‘primary cutaneous amyloidosis’ or ‘macular amyloidosis’ or ‘lichen amyloidosis’ or ‘nodular amyloidosis’ or ‘biphasic amyloidosis’ or ‘amyloidosis cutis dyschromica’. In total, twelve articles, including three original studies and nine case reports, were identified [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The dermoscopic characteristics of PCA are summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases, LA presented with central white hubs or scar-like centers surrounded by varied pigmentation, mainly in the form of gray-brown dots, globules, or peppering [ 2 , 7 , 11 , 12 ]. Behera et al [ 12 ] coined the term ‘two-zone pattern’ to describe this arrangement of dermoscopic structures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations